Method for culturing stem cells by using double-layer combined hydrogel microcarrier
By using a double-layer combined hydrogel microcarrier, using an inner gel structure formed by sodium alginate and carboxymethylcellulose and an outer gel structure formed by covalent cross-linking polymerization, the problem of existing gels in stem cells is solved. The problems of insufficient structural strength and short release time in culture enable more efficient stem cell culture.
Patent Information
- Application Number
- CN202410196600.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-19
- Filing Date
- 2024-02-22
- Publication Date
- 2025-01-21
AI Technical Summary
Existing gels have problems with insufficient structural strength and short release time in stem cell culture, resulting in limited stem cell culture efficiency.
A double-layer combined hydrogel microcarrier is used. The inner gel structure is formed by ionic cross-linking of sodium alginate and carboxymethyl cellulose. The outer gel structure is formed by covalent cross-linking polymerization to coat the inner gel. structure and embed nutrients in the inner gel structure.
It improves the structural strength of the gel, prolongs the release time of the contents, stably provides nutrients, and improves the culture efficiency of stem cells.
Smart Images

Figure CN119331810A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a double-layer composite hydrogel microcarrier and a manufacturing method and use thereof, and in particular to the use of the double-layer composite hydrogel microcarrier for culturing stem cells. Background Art
[0002] Gels have the characteristics of releasing the contents they carry and delaying the release, and are widely used in the field of drug release. However, existing gels are prone to disintegration and have insufficient structural strength, making it difficult to provide long-term and stable content release. Therefore, when gels are used to culture stem cells, the culture efficiency of stem cells is limited.
[0003] Therefore, how to provide a gel with enhanced structural strength and prolonged release time to improve stem cell culture efficiency is a problem to be solved. Summary of the invention
[0004] In some embodiments of the present disclosure, a method for culturing stem cells using a double-layer composite hydrogel microcarrier is provided, comprising: providing stem cells, a double-layer composite hydrogel microcarrier, and nutrients. The double-layer composite hydrogel microcarrier comprises: an inner layer gel structure, which is obtained by ionic crosslinking of an inner layer polymer via an inner layer crosslinker, wherein the inner layer polymer comprises a first inner layer polymer and a second inner layer polymer, the first inner layer polymer is sodium alginate, the second inner layer polymer is carboxymethyl cellulose, the weight ratio of sodium alginate to carboxymethyl cellulose is 3:2, and when the weight percentage of the inner layer gel structure is 100%, the weight percentage of carboxymethyl cellulose is greater than 1%; and an outer layer gel structure, which is obtained by covalent crosslinking polymerization of an outer layer monomer via an outer layer crosslinker, wherein the outer layer gel structure covers the inner layer gel structure, wherein the nutrients are located inside the inner layer gel structure; mixing the stem cells, the double-layer composite hydrogel microcarrier, and the nutrients to obtain a gelled culture medium; and adding the culture fluid to the gelled culture medium.
[0005] In some embodiments, the stem cells comprise embryonic stem cells, hematopoietic stem cells, mammary stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells, or a combination thereof.
[0006] In some embodiments, the inner layer gel structure is a plurality of inner layer sheet structures, and the inner layer sheet structures are connected to each other and spaced from each other by a plurality of inner layer holes; and the outer layer gel structure is a plurality of outer layer sheet structures, and the outer layer sheet structures are connected to each other and spaced from each other by a plurality of outer layer holes, wherein the pore size of each outer layer hole is smaller than the pore size of each inner layer hole.
[0007] In some embodiments, the inner layer gel structure exhibits an interpenetrating structure of the first inner layer polymer and the second inner layer polymer.
[0008] In some embodiments, the inner layer polymer and the inner layer cross-links have opposite electrical properties.
[0009] In some embodiments, the outer layer monomer comprises N,N-dimethylacrylamide, acrylamide, or a combination thereof.
[0010] In some embodiments, the outer layer cross-linker comprises N,N'-methylenebisacrylamide.
[0011] In some embodiments, when the weight percentage of the inner gel structure is 100%, the weight percentage of sodium alginate is 0.1% to 5%.
[0012] In some embodiments, when the weight percentage of the inner gel structure is 100%, the weight percentage of the carboxymethyl cellulose is 1% to 5%.
[0013] In some embodiments, the nutritional component comprises growth factors, vitamin A acid, penicillin, bovine serum albumin, or a combination thereof.
[0014] In some embodiments of the present disclosure, a method for culturing stem cells using a double-layer composite hydrogel microcarrier is provided, characterized in that it comprises: providing stem cells, a double-layer composite hydrogel microcarrier and nutrients, wherein the nutrients comprise macromolecular proteins having a molecular weight of at least greater than 500 g / mol, and the double-layer composite hydrogel microcarrier comprises: an inner layer gel structure, which is obtained by ionically crosslinking an inner layer polymer via an inner layer crosslinker, wherein the inner layer polymer comprises a first inner layer polymer and a second inner layer polymer, the first inner layer polymer is sodium alginate, and the second inner layer polymer is carboxymethyl cellulose, and the weight ratio of sodium alginate to carboxymethyl cellulose is 3:2; and an outer layer gel structure, which is obtained by covalently crosslinking and polymerizing an outer layer monomer via an outer layer crosslinker, wherein the outer layer gel structure covers the inner layer gel structure, and wherein the nutrients are located inside the inner layer gel structure; mixing the stem cells, the double-layer composite hydrogel microcarrier and the nutrients to obtain a gelled culture medium; and adding the culture solution to the gelled culture medium.
[0015] In some embodiments, the stem cells comprise embryonic stem cells, hematopoietic stem cells, mammary stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells, or a combination thereof.
[0016] In some embodiments, the inner layer gel structure is a plurality of inner layer sheet structures, and the inner layer sheet structures are connected to each other and spaced from each other by a plurality of inner layer holes; and the outer layer gel structure is a plurality of outer layer sheet structures, and the outer layer sheet structures are connected to each other and spaced from each other by a plurality of outer layer holes, wherein the pore size of each outer layer hole is smaller than the pore size of each inner layer hole.
[0017] In some embodiments, the inner layer gel structure exhibits an interpenetrating structure of the first inner layer polymer and the second inner layer polymer.
[0018] In some embodiments, the inner layer polymer and the inner layer cross-links have opposite electrical properties.
[0019] In some embodiments, the outer layer monomer comprises N,N-dimethylacrylamide, acrylamide, or a combination thereof.
[0020] In some embodiments, the outer layer cross-linker comprises N,N'-methylenebisacrylamide.
[0021] In some embodiments, when the weight percentage of the inner gel structure is 100%, the weight percentage of sodium alginate is 0.1% to 5%.
[0022] In some embodiments, when the weight percentage of the inner gel structure is 100%, the weight percentage of the carboxymethyl cellulose is greater than 1%.
[0023] In some embodiments, when the weight percentage of the inner gel structure is 100%, the weight percentage of the carboxymethyl cellulose is 1% to 5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to make the above and other objects, features, advantages and embodiments of the present invention more clearly understood, the accompanying drawings are described as follows:
[0025] Figure 1 A graph showing the change in gel state of ABA type triblock copolymer of poly(ε-caprolactone-co-glycolide)and poly(ethylene glycol; Tri-PCG) in some embodiments of the present disclosure when stored in phosphate buffered saline with changes in concentration and temperature.
[0026] Figure 2 Electron microscope images of the double-layer composite hydrogel microcarriers in some embodiments of the present disclosure are presented, wherein a to c in the top row are SA-CMC@PDMA-1 group, d to f in the second row are SA-CMC@PDMA-3 group, and g to i in the bottom row are SA-CMC@PAA-1 group.
[0027] Figure 3A It shows the water absorption and swelling characteristics of different inner gel structures.
[0028] Figure 3BThe water absorption and swelling properties of double-layer composite hydrogel microcarriers with different gel structures are presented.
[0029] Figure 4A , Figure 4B , Figure 5A , Figure 5B , Fig. 6A ,as well as Figure 6B The double-layer composite hydrogel microcarriers with different gel structures show the cumulative release rate of the contents over time at different pH values.
[0030] Figure 7 A graph showing the relationship between viscosity and temperature for gel structures having different weight percentages of sodium alginate and carboxymethyl cellulose is presented.
[0031] Fig. 8A The present invention shows the mRNA expression ratio of lipoprotein lipase (LPL) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) in adipose stem cells when adipose stem cells are cultured using gel structures with different weight ratios of sodium alginate and carboxymethyl cellulose.
[0032] Figure 8B A diagram showing the cell growth status under a microscope after adipose stem cells were cultured using gel structures with different weight ratios of sodium alginate and carboxymethyl cellulose and dyed purple-red. DETAILED DESCRIPTION
[0033] In order to make the description of the present invention more detailed and complete, the following describes in detail the implementation methods and specific embodiments of the present invention; however, this is not the only form of implementing or using the specific embodiments of the present invention. The various embodiments disclosed below can be combined or replaced with each other in beneficial situations, and other embodiments can be added to one embodiment without further description or explanation. In the following description, many specific details will be described in detail to enable the reader to fully understand the following embodiments. However, the embodiments of the present invention can be practiced without such specific details.
[0034] In this document, unless the context specifically limits the article, "a", "an" and "the" may refer to one or more. It will be further understood that "comprising", "including", "having" and similar words used in this document specify the features, regions, integers, steps, operations, elements and / or components described therein, but do not exclude other features, regions, integers, steps, operations, elements, components, and / or groups thereof.
[0035] As used herein, the term "about" means a value of a given amount that varies within 5% of the value (e.g., ±1%, ±2%, ±3%, ±4%, 5%). Such values are merely examples and are not intended to be limiting. It should be understood that the term "about" may mean a percentage of the value of a given amount as interpreted by one of ordinary skill in the art in view of the teachings herein.
[0036] Herein, if not otherwise specified, “%” refers to weight percentage (wt %).
[0037] Although a series of operations or steps are used below to illustrate the method disclosed herein, the order shown in these operations or steps should not be construed as a limitation of the present invention. For example, certain operations or steps may be performed in different orders and / or simultaneously with other steps. In addition, it is not necessary to perform all operations, steps and / or features to implement the embodiments of the present invention. Furthermore, each operation or step described herein may include several sub-steps or actions.
[0038] Some embodiments of the present disclosure provide a double-layer composite hydrogel microcarrier, comprising an inner gel structure and an outer gel structure. The inner gel structure is obtained by ionically crosslinking an inner polymer via an inner crosslinker. The outer gel structure is obtained by covalently crosslinking an outer monomer via an outer crosslinker, wherein the outer gel structure covers the inner gel structure.
[0039] The inner gel structure of the double-layer composite hydrogel microcarrier is an ionically cross-linked structure, which has the limitation that the structure is easily affected by the environmental pH value, or disintegrates due to the weakening of ionic force caused by water absorption and expansion. The outer gel structure formed by covalent bonding in the present disclosure can provide physical support for the inner gel structure, avoid the problem of structural instability of the inner gel structure, and enhance the structural strength of the double-layer composite hydrogel microcarrier. In addition, the outer gel structure can also serve as a barrier layer to further delay the release time of the carried contents (such as nutrient molecules), reduce the phenomenon of sudden release, and enable the carried contents to be released stably and for a long time.
[0040] In some embodiments, the outer gel structure is in the form of a porous membrane covering the inner gel structure to wrap the inner gel structure, wherein the thickness of the outer gel structure is smaller than that of the inner gel structure, and there is a van der Waals force between the outer gel structure and the inner gel structure to attract each other, but there is no covalent bonding.
[0041] In some embodiments, the inner gel structure is a plurality of inner sheet structures, and the inner sheet structures are connected to each other and spaced apart by a plurality of inner holes; and the outer gel structure is a plurality of outer sheet structures, and the outer sheet structures are connected to each other and spaced apart by a plurality of outer holes, wherein the pore size of each outer hole is smaller than the pore size of each inner hole. Through the pore size difference between the inner gel structure and the outer gel structure, the outer gel structure can have a better structural strength, and through the small pore size design of the outer gel structure, the double-layer combined hydrogel microcarrier is endowed with a better content sustained release effect.
[0042] In some embodiments, in a cross-sectional view, each inner layer lamellar structure (or outer layer lamellar structure) is arc-shaped, and the inner layer lamellar structures are opposite to each other with concave surfaces, thereby defining an inner layer hole (or outer layer hole). In some embodiments, the pore size of the inner layer hole represents the longest vertical distance between the two inner layer lamellar structures located on opposite sides of the inner layer hole; the pore size of the outer layer hole represents the longest vertical distance between the two outer layer lamellar structures located on opposite sides of the outer layer hole. In some embodiments, the pore size of the inner layer hole is 250 microns to 1000 microns, such as 250 microns, 500 microns, 750 microns, 1000 microns, or a value in the aforementioned interval. In some embodiments, the pore size of the outer layer hole is 50 microns to 500 microns, such as 50 microns, 100 microns, 150 microns, 200 microns, 250 microns, 300 microns, 350 microns, 400 microns, 450 microns, 500 microns, or a value in the aforementioned interval. If the pore size is too large, the structure will be unstable, the content release rate will be too fast, and sustained release cannot be achieved; if the pore size is too small, it will excessively block the content carried, making it difficult to achieve stable and long-term content release.
[0043] In some embodiments, the thickness of the outer gel structure is between 25 microns and 1000 microns, such as 25 microns, 50 microns, 100 microns, 200 microns, 300 microns, 400 microns, 500 microns, 600 microns, 700 microns, 800 microns, 900 microns, 1000 microns or values in the aforementioned intervals. If the thickness is too thick, the release rate of the carried content is too slow, and if the thickness is too thin, the release rate of the carried content is too fast and the structural strength is insufficient. It is understandable that as the thickness increases, the release of the contents (such as fat-soluble small molecules (molecular weight less than 500 g / mol, solubility in non-polar solvents greater than 0.1 micrograms / 1 gram) or macromolecular proteins (molecular weight at least greater than 500 g / mol) can be delayed.
[0044] In some embodiments, the inner layer polymer includes a first inner layer polymer and a second inner layer polymer, and the inner layer gel structure presents an interpenetrating structure of the first inner layer polymer and the second inner layer polymer (that is, the polymer chains of the first inner layer polymer and the second inner layer polymer are intertwined with each other). Through the design of the interpenetrating structure, better support can be provided to stabilize the structural strength of the inner layer gel structure.
[0045] In some embodiments, the inner layer polymer and the inner layer cross-linked material have opposite charges, for example, the inner layer polymer is negatively charged, the inner layer cross-linked material is positively charged, and the inner layer cross-linked material and the inner layer polymer are cross-linked via ionic bonding formed between the positive and negative charges to form an inner layer gel structure; or the inner layer polymer is positively charged, and the inner layer cross-linked material is negatively charged. When the inner layer polymer has different dissociation degrees at different pH values, the inner layer gel structure formed by ionic bonding cross-linking is pH-sensitive, and the strength of the ionic bonding will change due to changes in pH, thereby changing the inner layer gel structure.
[0046] In some embodiments, when the first inner layer polymer is sodium alginate (SA), the second inner layer polymer is carboxymethyl cellulose (CMC). The use of sodium alginate and carboxymethyl cellulose has the advantages of easy storage and preparation, safety and non-toxicity, gelation at room temperature, and easy absorption by the human body. In addition, compared with the use of sodium alginate alone, the combination of sodium alginate and carboxymethyl cellulose can improve the viscosity and structural strength of the inner layer gel structure, and by adjusting the ratio of sodium alginate and carboxymethyl cellulose, the pore size of the inner layer pores can be adjusted to provide better elasticity for the selection of the inner layer gel structure. In addition, when sodium alginate and carboxymethyl cellulose are selected, since sodium alginate and carboxymethyl cellulose have carboxyl groups, they are not easy to be free in an acidic environment. Therefore, the inner layer gel structure formed by the inner layer gel structure is denser, and the alkaline environment is more free, so the inner layer gel structure is looser.
[0047] In some embodiments, when the weight percentage of the inner gel structure is 100%, the weight percentage of sodium alginate is 0.1% to 5%, for example, 0.1%, 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, 2.75%, 3%, 3.25%, 3.5%, 3.75%, 4%, 4.25%, 4.5%, 4.75%, 5%, or a value in the aforementioned interval. The weight percentage of carboxymethyl cellulose is 0.1% to 5%, for example, 0.1%, 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, 2.75%, 3%, 3.25%, 3.5%, 3.75%, 4%, 4.25%, 4.5%, 4.75%, 5%, or values in the aforementioned range. When both are too high, the inner gel structure is too dense and the release efficiency of the inner gel structure is limited. When both are too low, the colloid structure is loose and unstable, or it cannot form gel. In addition, as the weight percentage of sodium alginate increases and the weight percentage of carboxymethyl cellulose decreases, the pore size of the inner pores will increase, increasing the expansion rate of the inner gel structure when absorbing water and the efficiency of content release; conversely, as the weight percentage of sodium alginate decreases and the weight percentage of carboxymethyl cellulose increases, the pore size of the inner pores will decrease, reducing the expansion rate and release efficiency of the inner gel structure (for example, reducing the release of large molecular proteins).
[0048] In some embodiments, when the first inner layer polymer is a poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer, the second inner layer polymer is a derivative of a poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer having an acyl group. In one embodiment, the poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer comprises an ABA-type triblock copolymer (Tri-PCG) of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol), and the acyl group is an acrylate group, and therefore, the derivative of a poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer having an acyl group is a poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer having an acrylate group (Tri-PCG-acryl). It is worth emphasizing that the inner gel structure of Tri-PCG and Tri-PCG-acryl can change the colloidal properties according to the change of temperature in the temperature range suitable for the human body (for example, from 25°C to 37°C, from solution to colloid), thereby changing the viscosity and release capacity of the inner gel structure, and the structure is relatively stable and not easy to disintegrate. In some embodiments, the double-layer composite hydrogel microcarrier also includes an inner layer auxiliary molecule (for example, dipentaerythritolhexakis (3-mercaptopropionate); DPMP) present in the inner gel structure. As the temperature gradually increases, DPMP can form a covalent structure with Tri-PCG-acryl, strengthen the colloidal properties, and improve the temperature sensitivity of the inner gel structure.
[0049] In some embodiments, when the weight percentage of the inner gel structure is 100%, the total weight percentage of Tri-PCG and Tri-PCG-acryl is 15% to 30%, such as 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or values in the aforementioned range. When the weight percentage is too high, the inner gel structure is too dense and the release efficiency of the inner gel structure is limited. When the weight percentage is too low, the colloid structure is loose and unstable, or it cannot form a gel.
[0050] In some embodiments, when the inner polymer is negatively charged, the inner crosslinks contain calcium ions (Ca 2+ ) can be cross-linked with the inner layer polymer. Compared with other inner layer cross-linking materials, calcium ions have the advantages of being easy to obtain, low cost, and less harmful to the environment.
[0051] In some embodiments, the outer layer monomer comprises N,N-dimethylacrylamide (DMAA), acrylamide (AA) or a combination thereof. Compared with AA, when DMAA is selected, the outer layer pores of the outer layer gel structure formed are larger, the release rate of the carried contents is higher (for example, the release rate of macromolecular proteins is increased), and the double-layer combined hydrogel microcarrier has a larger expansion rate when absorbing water.
[0052] In some embodiments, the outer crosslinker comprises N,N'-methylene-bisacrylamide (BIS), which can form a covalent bond with DMAA or AA, thereby crosslinking DMAA into poly(N,N-dimethylacrylamide) (poly(N,N-dimethylacrylamide; PDMA) or crosslinking AA into poly(acrylamide) (poly(acrylamide; PAA).
[0053] Some embodiments of the present disclosure provide a method for manufacturing a double-layer composite hydrogel microcarrier, comprising: providing an inner layer polymer and an inner layer crosslinking product; mixing the inner layer polymer and the inner layer crosslinking product, so that the inner layer polymer and the inner layer crosslinking product obtain an inner layer gel structure through ionic crosslinking; providing an outer layer monomer and an outer layer crosslinking product; mixing the inner layer gel structure, the outer layer monomer and the outer layer crosslinking product, so that the outer layer monomer and the outer layer crosslinking product obtain an outer layer gel structure through covalent crosslinking polymerization, and the outer layer gel structure covers the inner layer gel structure, thereby obtaining a double-layer composite hydrogel microcarrier. By mixing the inner layer gel structure, the outer layer monomer and the outer layer crosslinking product, an outer layer gel structure covering the inner layer gel structure can be formed, and the outer layer gel structure can provide physical support for the inner layer gel structure, improve the structural strength of the double-layer composite hydrogel microcarrier, and delay the release time of the carried content, so as to achieve stable and long-term release.
[0054] In some embodiments, the step of providing an inner layer polymer and an inner layer cross-linker comprises providing a first inner layer polymer, a second inner layer polymer, and an inner layer cross-linker.
[0055] In some embodiments, the first inner layer polymer is sodium alginate (SA) and the second inner layer polymer is carboxymethyl cellulose (CMC), which has the advantages of easy storage and preparation, safety and non-toxicity, gelation at room temperature, and easy absorption by the human body.
[0056] In some embodiments, when the first inner layer polymer is a copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol), the second inner layer polymer is a derivative of a copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) having an acyl group. In one embodiment, the copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) comprises an ABA-type triblock copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) (Tri-PCG), and the derivative of the copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) having an acyl group is a copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) having an acrylate group (Tri-PCG-acryl). The inner gel structure made of Tri-PCG and Tri-PCG-acryl is relatively dense, and the colloidal properties can change according to the change of temperature within the temperature range suitable for the human body (for example, from 25°C to 37°C, from solution to colloid), thereby changing the viscosity and release ability of the inner gel structure, and the structure is relatively stable and not easy to disintegrate.
[0057] In some embodiments, the inner layer polymer and the inner layer cross-links have opposite charges. In some embodiments, when the inner layer polymer is negatively charged, the inner layer cross-links contain calcium ions.
[0058] In some embodiments, the step of mixing the inner layer polymer and the inner layer crosslinking material comprises mixing a first inner layer polymer, a second inner layer polymer, an inner layer crosslinking material, a free radical generator, and water. By adding the free radical generator in this step, the free radical generator stored in the inner layer gel structure can diffuse to the outer layer when the outer layer monomer, the outer layer crosslinking material, and the catalyst are subsequently added, and react with the outer layer monomer, the outer layer crosslinking material, and the catalyst, thereby inducing a reaction in the outer layer to form the outer layer gel structure. Therefore, adding the free radical generator in this step can avoid premature reaction when the free radical generator is co-added with the outer layer monomer, the outer layer crosslinking material, and the catalyst, or the situation where the outer layer gel structure does not well cover the inner layer gel structure.
[0059] In some embodiments, the weight ratio of the first inner layer polymer to the second inner layer polymer is 1:5 to 5:1, such as 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or values in the aforementioned ranges. When the first inner layer polymer has more free negatively charged groups (such as carboxyl groups) in an alkaline environment relative to an acidic environment, the expansion rate of the inner gel structure is higher as the weight ratio increases.
[0060] In some embodiments, the step of mixing the inner layer polymer and the inner layer cross-linking material comprises mixing a first inner layer polymer, a second inner layer polymer, an inner layer cross-linking material, a free radical generator and water.
[0061] In some embodiments, when the weight percentage of the sum of the first inner layer polymer, the second inner layer polymer, the inner layer cross-linking material, the free radical generator and water is 100%, the weight percentage of sodium alginate is 0.1% to 5%, and the weight percentage of carboxymethyl cellulose is 0.1% to 5%. When the weight percentage is too high, the inner layer gel structure is too dense, and the release efficiency of the inner layer gel structure is limited. When the weight percentage is too low, the colloid structure is loose and unstable, or it cannot form a gel. When the weight percentage of carboxymethyl cellulose is greater than 1% (for example, 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, 2.75%, 3%, 3.25%, 3.5%, 3.75%, 4%, 4.25%, 4.5%, 4.75%, 5%, or a value in the aforementioned range), the double-layer combined hydrogel microcarrier can be given sufficient structural strength for continuous culturing of stem cells for multiple days without disintegration. In some embodiments, when the weight ratio of sodium alginate to carboxymethyl cellulose is 3:2, the pore size of the inner gel structure can be controlled so that nutrients are stably released at an appropriate rate, thereby ensuring that stem cells stably absorb nutrients, thereby increasing the growth rate of stem cells.
[0062] In some embodiments, when the weight percentage of the total of the first inner layer polymer, the second inner layer polymer, the inner layer cross-linking material, the free radical generator and water is 100%, the weight percentage of the total of the poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer and the derivative of the poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer with acyl group is 15% to 30%. When the weight percentage is too high, the inner layer gel structure is too dense and the release efficiency of the inner layer gel structure is limited. When the weight percentage is too low, the gel structure is loose and unstable, or cannot be gelled.
[0063] In some embodiments, the step of mixing the first inner layer polymer, the second inner layer polymer, the inner layer crosslinker, the free radical generator, and water further comprises adding dipentaerythritol hexa(3-thiol propionate), fetal bovine serum albumin, or a combination thereof. In some embodiments, the step of mixing the first inner layer polymer, the second inner layer polymer, the inner layer crosslinker, the free radical generator, and water comprises mixing a first solution, a second solution, calcium ions, and ammonium sulfate, wherein the first solution comprises poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer, or poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer and dipentaerythritol hexa(3-thiol propionate) (DPMP), and the second solution comprises a derivative of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) copolymer having an acyl group and fetal bovine serum albumin.
[0064] It is understandable that, as the temperature increases, DPMP tends to form a covalent bond with the acyl group, thereby increasing the density of the inner gel structure. Therefore, by adding DPMP, the sustained release capacity of the inner gel structure can be increased when the temperature increases, which is beneficial for use in the human body. In some embodiments, when the weight percentage of the first solution is 100%, the weight percentage of DPMP is 5% to 15%, such as 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or a value in the aforementioned interval. In addition, by adding fetal bovine serum albumin, the fetal bovine serum albumin can be coated in the double-layer composite hydrogel microcarrier. When the double-layer composite hydrogel microcarrier is used for cell culture, the fetal bovine serum albumin can be continuously released to provide a cell nutrient source for a long time.
[0065] In some embodiments, the step of mixing the inner gel structure, the outer monomer and the outer crosslinker comprises mixing the inner gel structure, N,N-dimethylacrylamide (DMAA), N,N'-methylenebisacrylamide (BIS) and a catalyst, or mixing the inner gel structure, acrylamide (AA), N,N'-methylenebisacrylamide and a catalyst. The covalent outer gel structure formed by BIS and DMAA or AA can enhance the physical support of the inner gel structure and form denser pores than the inner gel structure, thereby prolonging the release of the carried contents.
[0066] In some embodiments, when the sum of the weight percentages of the inner gel structure, the outer monomer, and the outer crosslink is 100%, the weight percentage of the inner gel structure is 50% to 80% (e.g., 50%, 60%, 70%, 80% or values in the aforementioned intervals), the weight percentage of the outer monomer is 15% to 40% (e.g., 15%, 20%, 25%, 30%, 35%, 40% or values in the aforementioned intervals), and the weight percentage of the outer crosslink is 5% to 10% (e.g., 5%, 6%, 7%, 8%, 9%, 10% or values in the aforementioned intervals). If the weight percentage of the inner gel structure or the outer gel structure is too low, it is difficult to form a double-layer combined hydrogel microcarrier. If the weight percentage of the inner gel structure or the outer gel structure is too high, the release rate of the contents carried by the double-layer combined hydrogel microcarrier is too low.
[0067] In some embodiments, the weight ratio of the inner gel structure to the outer monomer is 5:4 to 16:3 (e.g., 5:4, 5:3, 2:1, 8:3, 10:3, 4:1, 16:3, 16:3 or values in the aforementioned intervals). If the weight ratio is too high, the structure of the double-layer combined hydrogel microcarrier is unstable; if the weight ratio is too low, the outer layer of the double-layer combined hydrogel microcarrier is too thick, and the release rate of the carried content is too low.
[0068] In some embodiments, in the step of mixing the inner gel structure, the outer monomer and the outer crosslinked material, the mixing time is 0.5 minutes to 5 minutes, such as 0.5 minutes, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, or values in the aforementioned intervals. By controlling the mixing time, the thickness of the outer gel structure can be controlled, thereby controlling the structural strength and release rate of the double-layer combined hydrogel microcarrier.
[0069] Some embodiments of the present disclosure also provide a method for culturing stem cells using the aforementioned double-layer composite hydrogel microcarrier, comprising: providing stem cells, a double-layer composite hydrogel microcarrier and nutrients, the double-layer composite hydrogel microcarrier comprising: an inner gel structure and an outer gel structure. The inner gel structure is obtained by ionically crosslinking an inner polymer via an inner crosslinker, wherein the inner polymer comprises a first inner polymer and a second inner polymer, the first inner polymer is sodium alginate, the second inner polymer is carboxymethyl cellulose, the weight ratio of sodium alginate to carboxymethyl cellulose is 3:2, and when the weight percentage of the inner gel structure is 100%, the weight percentage of carboxymethyl cellulose is greater than 1%; and an outer gel structure is obtained by covalently crosslinking and polymerizing an outer monomer via an outer crosslinker, wherein the outer gel structure covers the inner gel structure, wherein the nutrients are located inside the inner gel structure; mixing the stem cells, the double-layer composite hydrogel microcarrier and the nutrients to obtain a gelled culture medium; and adding the culture fluid to the gelled culture medium. By controlling the weight percentage of carboxymethyl cellulose, the double-layered hydrogel microcarrier can be given better structural stability, and by defining the weight ratio of sodium alginate to carboxymethyl cellulose and the position of the nutrients, the release time of the nutrients carried can be extended. Therefore, when using double-layered hydrogel microcarriers to culture stem cells, it can maintain a longer time before disintegration, increase the amount of stem cell culture per unit area, and avoid sudden release of contents. The contents can be continuously released to the stem cells, thereby extending the stem cell culture time and the number of times to add nutrients, simplifying the culture process.
[0070] In some embodiments, the stem cells comprise embryonic stem cells, hematopoietic stem cells, mammary stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells, or a combination thereof.
[0071] It is understandable that, according to the different characteristics of stem cells, double-layer combined hydrogel microcarriers with different structural strengths and release rates can be selected. For example, when culturing adipose stem cells with a faster growth rate, sodium alginate and carboxymethyl cellulose with larger inner pores can be selected, and when culturing neural stem cells with a slower growth rate, Tri-PCG and Tri-PCG-acryl with smaller inner pores can be selected.
[0072] To further illustrate the double-layered combined hydrogel microcarriers, methods for making double-layered combined hydrogel microcarriers, and methods for culturing stem cells provided by various embodiments of the present disclosure, the following examples are performed. It should be noted that the following examples are provided for demonstration purposes only and are not intended to limit the present invention.
[0073] Example 1: Method for manufacturing double-layer combined hydrogel microcarrier
[0074] 1. Inner gel structure
[0075] The following provides the processes corresponding to different inner layer polymers.
[0076] 1.1. Sodium alginate and carboxymethyl cellulose
[0077] Sodium alginate (SA) and carboxymethyl cellulose (CMC) were mixed in different weight ratios (SA:CMC = 4:1, 2:3, 3:2, 1:4), and then poured into a 5% calcium chloride aqueous solution (calcium chloride; CaCl2) containing 1.5% ammonium persulfate (APS) to form a mixed solution, which was stirred for 20 minutes to allow SA and CMC to be cross-linked via calcium ions to form multiple groups of inner layer gel structures with different SA and CMC concentrations to obtain inner layer hydrogels. The SA and CMC of each group were 2.0% / 0.5%, 1.0% / 1.5%, 1.5% / 1.0%, 0.5% / 2.0%, respectively, the reaction concentration of APS was 1%, and the reaction concentration of calcium ions was 4%.
[0078] It is understandable that in the process of forming the mixed solution (not limited to the example of using sodium alginate and carboxymethyl cellulose as the inner layer polymer), culture medium or nutrients (such as growth factors) can be added to the mixed solution according to the subsequent stem cell culture requirements, and the final concentration of the nutrients can be made to fall between 5 mg / ml and 10 mg / ml for subsequent clinical applications.
[0079] 1.2 ABA-type triblock copolymers of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) (Tri-PCG) and Tri-PCG derivatives with acrylate groups (or Tri-PCG-acryl)
[0080] 1.2.1 Preparation of Tri-PCG
[0081] Poly(ethylene glycol) (PEG) (15.0 g, 10 mmol) was dried under reduced pressure at 120° C. for 3 hours. ε-caprolactone (33.3 g, 291 mmol), glycolide (5.87 g, 50.6 mmol) and tin2-ethylhexanoate (Sn(Oct)2) (149 mg, 367 μmol) as a catalyst were added to the flask containing PEG to obtain a reaction solution.
[0082] Next, the reaction solution was frozen with liquid nitrogen and dried under reduced pressure to obtain a reactant. Subsequently, the flask containing the reactant was immersed in a 160°C oil bath for 12 hours to carry out a ring-opening polymerization reaction. Next, the reactant was dissolved in 100 ml of chloroform and precipitated with 1000 ml of diethyl ether, and the dissolution step and precipitation step were repeated 3 times. Next, the supernatant was removed, and the precipitate was dried under reduced pressure to obtain a white solid, which was Tri-PCG.
[0083] 1.2.2 Preparation of Tri-PCG-acryl
[0084] Acrylic acid (2.0 ml, 29.2 mmol) was dissolved in 250 ml of dichloromethane (CH2Cl2) to obtain an acrylic acid solution; and N,N'-dicyclohexyl carbodiimide (DCC) (6.24 g, 30.2 mmol) was dissolved in 250 ml of dichloromethane to obtain an N,N'-dicyclohexyl carbodiimide solution. Then, in an ice bath, the N,N'-dicyclohexyl carbodiimide solution was added to the acrylic acid solution and stirred for 1 hour, wherein the volume ratio of the N,N'-dicyclohexyl carbodiimide solution to the acrylic acid solution was 1:1. Next, Tri-PCG (20.3 g, 5.1 mmol) and 4-dimethylaminopyridine (DMAP) (299.5 mg, 2.5 mmol) dissolved in 250 ml of dichloromethane were added to the mixed solution containing acrylic acid and N,N'-dicyclohexylcarbodiimide and stirred at 25°C for 24 hours. Subsequently, the by-product dicyclohexylurea was filtered out. After the dichloromethane was evaporated, chloroform was used as a good solvent (a solvent with strong solubility for the solute and an interaction parameter with the polymer solute of less than 0.5) to make the polymer long chain in the solution stretched, and a mixture of n-hexane and ethanol (the volume ratio of n-hexane to ethanol was 8 / 2) was used as a poor solvent (a solvent with weak solubility for the solute and an interaction parameter with the polymer solute of close to or greater than 0.5), and reprecipitation was performed three times. Then, the product was dried under reduced pressure to obtain Tri-PCG-acryl as a yellow-white solid.
[0085] 1.2.3 Preparation of Tri-PCG aqueous solution, Tri-PCG-acryl aqueous solution and Tri-PCG / DPMP aqueous solution
[0086] For Tri-PCG aqueous solution: First, Tri-PCG (246.5 mg) was dissolved in adipose stem cell culture medium (986 μL, product name: StemPro TM MSC SFM, Product No.: Gibco TMA1033201). After soaking in a water bath at about 90°C for 5 seconds, continue stirring and cool at room temperature, repeat the soaking and cooling steps three times. Then, cool in a water bath (20°C to 25°C), perform ultrasonic treatment for 30 minutes to remove bubbles, and use sodium hydroxide and adipose stem cell culture medium to adjust the pH value to 7.4 to obtain a 20% Tri-PCG aqueous solution (which can be replaced with the subsequent Tri-PCG / DPMP aqueous solution according to colloid requirements).
[0087] For Tri-PCG-acryl aqueous solution: Tri-PCG-acryl (165 mg) was dissolved in adipose stem cell culture medium (660 μL) containing 10% fetal bovine serum and stirred overnight at 4°C. Then, ultrasonic treatment was performed for 30 minutes at low temperature (20°C to 25°C) to remove bubbles, and the pH value was adjusted to 7.4 using sodium hydroxide and adipose stem cell culture medium to obtain a 20% Tri-PCG-acryl aqueous solution.
[0088] For Tri-PCG / DPMP aqueous solution: Dissolve dipentaerythritolhexakis(3-mercaptopropionate) (DPMP) (90.4 mg) in 1 ml of acetone to obtain a DPMP solution. Add the DPMP solution to a sample tube containing 750 mg of Tri-PCG, and add 7 ml of acetone to obtain a mixed solution. Add the mixed solution to 63 ml of water, stir and ultrasonicate for 30 minutes, then remove the acetone and freeze-dry to obtain a Tri-PCG / DPMP mixture (DPMP accounts for about 10.8% in the Tri-PCG / DPMP mixture).
[0089] Next, the Tri-PCG / DPMP mixture was dissolved in adipose stem cell culture medium (354 μL) containing 10% fetal bovine serum. After being immersed in a water bath at about 90°C for 5 seconds, the mixture was stirred continuously and cooled at room temperature, and the immersion and cooling steps were repeated three times. Next, an ultrasonic treatment was performed at low temperature (20°C to 25°C) for 30 minutes to remove bubbles, and the pH value was adjusted to 7.4 using sodium hydroxide and adipose stem cell culture medium to obtain a 20% Tri-PCG / DPMP aqueous solution.
[0090] 1.2.4 Preparation of inner layer hydrogel
[0091] After the Tri-PCG / DPMP aqueous solution and the Tri-PCG-acryl aqueous solution are mixed in an appropriate proportion, the solution is poured into a 5% calcium chloride aqueous solution (calcium chloride; CaCl2) containing 1.5% ammonium persulfate (AMS) to form a mixed solution, which is stirred for 20 minutes to allow Tri-PCG and Tri-PCG-acryl to be cross-linked via calcium ions to form an inner gel structure, thereby obtaining an inner hydrogel, wherein the reaction concentrations of Tri-PCG / DPMP and Tri-PCG-acryl are 70% to 79% and 16% to 25% respectively, the reaction concentration of APS is 1%, the reaction concentration of calcium ions is 4%, and the total weight percentage of the inner gel structure Tri-PCG and Tri-PCG-acryl is 16% to 33%, so as to ensure that the inner hydrogel is in a colloidal state within the action temperature range.
[0092] It can be understood that as the temperature increases, the acrylate groups of Tri-PCG and Tri-PCG-acryl, or DPMP and Tri-PCG-acryl can produce covalent bonds, thereby changing the gel morphology. Therefore, the inner membrane gel structure prepared using Tri-PCG-acryl and Tri-PCG / DPMP, or using Tri-PCG-acryl and Tri-PCG, is temperature sensitive.
[0093] For example, see Figure 1 , is a graph showing the change in the gel state of Tri-PCG at different concentrations and temperatures (the Tri-PCG in this example is stored in phosphate buffered saline (PBS)), showing that the gel state is changed by adjusting the Tri-PCG concentration (e.g., corresponding to the sum of the concentrations of Tri-PCG / DPMP and Tri-PCG-acryl in this embodiment) or temperature, and the viscosity and release ability of the gel are adjusted according to the change in the gel state.
[0094] In other examples, a Tri-PCG aqueous solution may be used instead of a Tri-PCG / DPMP aqueous solution and mixed with Tri-PCG-acryl. It can be understood that, compared with a Tri-PCG aqueous solution, since a Tri-PCG / DPMP aqueous solution contains DPMP that can covalently bond with Tri-PCG-acryl when heated, the inner membrane gel structure prepared using a Tri-PCG / DPMP aqueous solution has better temperature sensitivity.
[0095] It is understandable that the difference between the inner gel structure prepared by "1.1, sodium alginate and carboxymethyl cellulose" and the inner gel structure prepared by "1.2 ABA-type triblock copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) (Tri-PCG) and Tri-PCG derivative with acrylate group (or Tri-PCG-acryl)" is that the inner gel structure using Tri-PCG / DPMP and Tri-PCG-acryl is more stable and not easy to disintegrate, but the preparation process is more complicated and requires the use of organic solvents. As for the inner gel structure using SA and CMC, it has the advantages of simpler preparation process and higher environmental friendliness, but there is a limitation that the structure is also affected by pH value.
[0096] Therefore, appropriate ingredients can be selected to prepare the inner gel structure according to the growth characteristics of the stem cells to be cultured subsequently. For example, SA and CMC, which are easy to prepare, can be used to culture adipose stem cells with faster growth rates, while Tri-PCG / DPMP and Tri-PCG-acryl, which have stronger structural strength, can be used to culture neural stem cells with slower growth rates.
[0097] 2. Outer gel structure and double-layer combined hydrogel microcarriers
[0098] Next, after mixing N,N-dimethylacrylamide (DMAA) or acrylamide (AA) as an outer layer monomer, N,N'-methylenebisacrylamide (BIS) as an outer layer crosslinker, and tetramethylethylenediamine (TEMED) as a catalyst, the previously prepared inner layer hydrogel (herein, the inner layer hydrogel obtained by "1.1, sodium alginate and carboxymethyl cellulose") is added and mixed for different time periods so that DMAA or AA and BIS are crosslinked to form poly(N,N-dimethylacrylamide) (PDMA) or poly(acrylamide) (PAA), thereby obtaining a double-layer composite hydrogel microcarrier with different outer layer gel structure thicknesses or different outer layer components, wherein the reaction concentration of DMAA or AA is 1 mol / L, the reaction concentration of BIS is 2.2 mol / L, and the reaction concentration of TEMED is 15 mg / mL.
[0099] Specifically, during the mixing process, the APS in the inner hydrogel diffuses to the outside, providing free radicals to initiate the reaction of forming the outer gel structure. The outer monomers are covalently bonded to BIS to form PDMA or PAA through the free radicals of APS and the catalysis of TEMED, forming the outer gel structure.
[0100] Finally, unreacted outer layer monomers are removed by stirring and washing with water.
[0101] Example 2: Method for culturing stem cells using double-layer combined hydrogel microcarriers
[0102] First, the 1x10 7 Adipose stem cell suspension (i.e., adipose stem cells suspended in adipose stem cell culture medium) containing 100 g / ml of adipose stem cells and a double-layer combined hydrogel microcarrier were mixed in a volume ratio of 1:1 to form a stem cell mixed gel, and allowed to stand at 37°C for 30 minutes to enhance the degree of gelation.
[0103] Next, 400 microliters of adipose stem cell culture fluid was dropped onto the surface of the stem cell mixed gel and placed in an environment at 37°C with 5% carbon dioxide for culture. Every 2 days, 200 microliters of adipose stem cell culture fluid (supernatant) was taken out and replaced with fresh adipose stem cell culture fluid. After the double-layer combined hydrogel microcarriers were ruptured, the adipose stem cells were collected using PBS and other culture components were removed.
[0104] It can be understood that the setting of the outer gel structure can provide physical stability for the inner gel structure, preventing the inner gel structure from swelling and rupture due to water absorption or structural disintegration when alkaline, while avoiding excessive release and leakage of nutrients and maintaining stable release of nutrients.
[0105] Example 3, efficacy test
[0106] First, a double-layered composite hydrogel microcarrier was prepared according to the method of Example 1, and the specific components, weight percentages, and the formation time of the outer gel structure (i.e., the mixing time in "2. Outer gel structure and double-layered composite hydrogel microcarrier") were adjusted to compare the differences in structural characteristics and content release efficiency between different double-layered composite hydrogel microcarriers. Examples of each group of conditions are as follows:
[0107] Table 1. Test group conditions
[0108]
[0109] 1. Gel morphology under electron microscope
[0110] First, the double-layered hydrogel microcarriers of each group were observed at different magnifications using a scanning electron microscope. Figure 2 , among which a to c in the top row are SA-CMC@PDMA-1 group, d to f in the second row are SA-CMC@PDMA-3 group, and g to i in the bottom row are SA-CMC@PAA-1 group.
[0111] Figure 2It can be seen that the inner layer and the outer layer of the double-layer composite hydrogel microcarrier are both connected to each other in a sheet-like structure, separated by three-dimensional holes, and there is a clear boundary between the inner layer and the outer layer. In addition, the inner layer gel structure and the outer layer gel structure have different hole sizes, and the pore size of the outer layer gel structure is smaller than that of the inner layer gel structure.
[0112] In addition, by comparing Figure c (SA-CMC@PDMA-1 group) and Figure f (SA-CMC@PDMA-3 group), it can be found that when the outer layer cross-linking time increases from 1 minute to 3 minutes, the thickness of the outer layer gel structure increases from about 100 microns to about 450 microns.
[0113] In addition, by comparing Figure b (SA-CMC@PDMA-1 group) and Figure e (SA-CMC@PDMA-3 group), it can be found that as the SA concentration decreases, the pore diameters of the inner and outer layers change significantly. The higher the SA ratio, the larger the pore diameter of the inner layer.
[0114] according to Figure 2 It can be understood that the double-layer composite hydrogel microcarrier has a double-layer skeleton structure. The pores of the inner gel structure are larger, which is conducive to the adsorption of nutrients. The outer gel structure is denser, which can provide physical support for the inner gel structure, avoid the disintegration of the inner gel structure, and avoid excessive release of nutrients. Therefore, the double-layer composite hydrogel microcarrier can provide a scaffold for the three-dimensional growth of stem cells and retain nutrients for a long time, increase the number of stem cells cultured and prolong the sustainable culture time. The following will further verify the relevant efficacy.
[0115] 2. Water absorption and expansion
[0116] In order to detect the water absorption and swelling properties of the inner gel structure alone (single-layer gel) and the double-layer composite hydrogel microcarriers, the inner gel structure (four groups, the SA concentration and CMC concentration of each group were 0.5% SA / 2.0% CMC, 1.0% SA / 1.5% CMC, 1.5% SA / 1.0% CMC, 2.0% SA / 0.5% CMC) and the double-layer composite hydrogel microcarriers (SA-CMC@PDMA-1 group, SA-CMC@PDMA-2 group, SA-CMC@PDMA-3 group, SA-CMC@PAA-1 group) were naturally air-dried, and an appropriate amount of the air-dried inner gel structure and the air-dried double-layer composite hydrogel microcarriers (hereinafter referred to as samples) were weighed for swelling test, and the process is as follows.
[0117] First, the sample was placed in an acidic solution (0.5 M hydrochloric acid) with a pH value of 1.2 for 2 hours, and then switched to an alkaline solution (1 M tris(hydroxymethyl)aminomethane) with a pH value of 7.4) until the weight reached equilibrium or decreased (indicating the beginning of dissolution). During the process, the sample was taken out of the solution every 30 minutes, and the residual solution was removed and weighed. The swelling ratio SR (swelling ratio) at each time point was calculated using the following formula.
[0118] SR=[(m0-mt) / m0]
[0119] SR is the swelling ratio of the double-layer combined hydrogel microcarrier, mt is the mass of the double-layer combined hydrogel microcarrier at time point t (swollen state), and m0 is the initial mass of the hydrogel.
[0120] According to the expansion rate trend of the inner gel structure obtained from the above test, please refer to Figure 3A For the trend of the expansion rate of the double-layer combined hydrogel microcarrier, please refer to Figure 3B .
[0121] Figure 3A The water absorption and swelling characteristics of different inner gel structures are shown. The swelling rates of the four inner gel structures in an acidic environment are low because there are more carboxyl groups (-COOH) in SA and CMC, but in acidic solutions, the carboxyl groups are less free, the electrostatic repulsion between polymers is lower, the gel network structure is dense, and the hydrophilicity of SA and CMC decreases. Therefore, compared with alkaline solutions, the swelling rate of the inner gel structure (single-layer gel) is lower in acidic solutions. In addition, it can be observed that in acidic solutions, as the CMC concentration decreases, the swelling rate also decreases.
[0122] In contrast, in an alkaline environment, the expansion rate increases with time, gradually increases, and then decreases. Specifically, the carboxyl group is in a free state (COO - ), electrostatic repulsion is formed between carboxyl groups, and increases with time, causing the monolayer gel to swell and expand the network gap, changing the structure, increasing hydrophilicity, and absorbing water molecules, thereby increasing the swelling rate. In the later stage of the action, as the structure changes, the ionic crosslinking formed by carboxyl groups and calcium ions becomes increasingly unstable, and the carboxyl concentration decreases, which in turn leads to a weaker crosslinking reaction between carboxyl groups and calcium ions, causing the monolayer gel to gradually disintegrate.
[0123] Figure 3B The water absorption and swelling characteristics of the double-layer combined hydrogel microcarriers with different gel structures are presented. Figure 3A The water absorption and swelling time (the time from water absorption to disintegration) of the single-layer gel (only the inner gel structure) is 4.5 hours. Figure 3BThe water absorption and swelling time of the double-layer composite hydrogel microcarrier was significantly extended to 12 hours, and the overall swelling rate was higher than that of the single-layer gel. In other words, although the inner gel structure of the double-layer composite hydrogel microcarrier is sensitive to pH value, the outer gel structure is less sensitive to pH value. Therefore, even in an alkaline environment, the outer gel structure can maintain the integrity of the gel structure and is not easy to disintegrate.
[0124] In addition, by comparing the SA-CMC@PDMA-2 group (outer layer cross-linking time 2 hours) and the SA-CMC@PDMA-3 group (outer layer cross-linking time 3 hours), it can be found that by increasing the outer layer cross-linking time to increase the thickness of the outer layer gel structure, the disintegration of the gel can be delayed.
[0125] Comparing the SA-CMC@PDMA-1 group (1.5% SA / 1.0% CMC) and the SA-CMC@PDMA-2 group (0.5% SA / 2.0% CMC), it can be found that the group with reduced SA concentration has a lower swelling rate after 4 hours. Therefore, in an alkaline environment, reducing the SA concentration can be used as a means to prolong the release time of nutrients.
[0126] Finally, by comparing the SACMC@PDMA-1 group (PDMA) and the SA-CMC@PAA-1 group (PAA), it can be found that compared with PAA, PDMA as the outer gel structure exhibits a higher swelling rate and has better water absorption and swelling capacity.
[0127] 3. Content release behavior
[0128] 3.1 Test Method
[0129] In order to test the content release behavior of each group of double-layer combined hydrogel microcarriers, a content release test was performed according to the following procedure.
[0130] First, three contents with different molecular weights and solubility characteristics were selected and mixed with different groups of double-layer composite hydrogel microcarriers, so that the double-layer composite hydrogel microcarriers carried each content, wherein the contents were selected from tretinoin (TR) to represent the fat-soluble component, ampicillin (AM) to represent the water-soluble component, and bovine serum albumin (BS) to represent the component of stem cell culture medium, the concentration of tretinoin in the double-layer composite hydrogel microcarrier was 0.5 mg / L, the concentration of ampicillin in the double-layer composite hydrogel microcarrier was 100 mg / mL, and the weight percentage of bovine serum albumin in the double-layer composite hydrogel microcarrier was 5%. The double-layer composite hydrogel microcarrier carrying the contents was immersed in an acidic solution with a pH value of 1.2 for 2 hours, and then transferred to a weakly alkaline solution with a pH value of 7.4 at 36.5°C±0.5°C. Next, the double-layered hydrogel microcarriers were weighed and immersed in 100 ml of PBS. They were rotated and shaken at an appropriate speed at a temperature of 36.5°C ± 0.5°C. A certain amount of PBS was extracted at regular intervals and the content concentration was measured using an ultraviolet spectrophotometer (TR measurement wavelength 350 nanometers, AM measurement wavelength 463 nanometers, BS measurement wavelength 595 nanometers), and an equal amount of PBS was added. Next, the cumulative content release rate Qn of the double-layered hydrogel microcarriers was measured according to the following formula, and the results were organized in 4A to 6B .
[0131] Qn(%)=(V0Cn+VC(n-1)) / (W)x100
[0132] Cn and C(n-1) are the content concentrations of the nth and n-1st samplings, V0 is the initial volume of PBS, V is the sampling volume, and W is the weight of the content loaded in the double-layer combined hydrogel microcarrier.
[0133] 3.2 Results Analysis
[0134] In order to understand the effects of the composition, weight percentage and outer layer cross-linking time of the double-layer composite hydrogel microcarrier on the content release behavior, the following will be Figure 4A (SA-CMC@PDMA-2) and Figure 4B (SA-CMC@PDMA-3), Figure 5A (SA-CMC@PDMA-1) and Figure 5B (SA-CMC@PDMA-2), and Fig. 6A (SA-CMC@PDMA-1) and Figure 6B (SA-CMC@PAA-1) are discussed in a comparative manner.
[0135] 3.2.1. Comparison of outer layer thickness on the release behavior of contents
[0136] First, please refer to Figure 4A as well as Figure 4B The difference between the two groups of double-layer combined hydrogel microcarriers is that the cross-linking time of the outer layer is extended from 2 minutes (SA-CMC@PDMA-2 group) to 3 minutes (SA-CMC@PDMA-3 group), which increases the thickness of the outer gel structure.
[0137] Figure 4A as well as Figure 4B The results showed that in the initial acidic environment, the two double-layer combined hydrogel microcarriers had good sustained release effects on fat-soluble vitamin A acid (TR) and bovine serum albumin (BS), but did not have the same control effect on water-soluble penicillin (AM). AM has a serious release effect due to its small molecular weight and easy diffusion into the solution. In the SA-CMC@PDMA-2 group, the release rate in 2 hours was as high as about 90%, while in the SA-CMC@PDMA-3 group with a thicker outer layer, the release rate in 2 hours was about 65% due to increased diffusion resistance, which means that the thickness of the outer layer still has a delayed release effect on the water-soluble component AM in an acidic environment.
[0138] In a weakly alkaline environment, the inner gel structure begins to absorb water and swell, and the network structure collapses, thereby gradually releasing vitamin A acid (TR) and bovine serum albumin (BS). In the SA-CMC@PDMA-2 group, the TR release rate reached more than 90% at 36 hours, while the release rate of BS, which has a larger molecular structure, only reached about 64%, indicating that the double-layer structure design has a better sustained release effect on the stem cell culture fluid components (represented by BS) than the fat-soluble components (represented by TR). Relatively speaking, in the SA-CMC@PDMA-3 group with a thicker outer layer, the TM release rate dropped to about 80% at 36 hours, and the BS release rate only reached 35%, indicating that in a weakly alkaline environment, it can better play a role in delaying and controlling the release of fat-soluble components (TR) and stem cell culture fluid components (BS).
[0139] Therefore, according to Figure 4A as well as Figure 4B , it can be understood that by increasing the thickness of the outer layer, the diffusion resistance can be increased, thereby significantly delaying the release of the contents.
[0140] 3.2.2 Comparison of the inner layer composition concentration on the content release behavior
[0141] Please refer to Figure 5A as well as Figure 5BThe difference between the two groups of double-layer composite hydrogel microcarriers is that the weight percentage of the inner layer polymer is different (1.5% SA / 1.0% CMC in the SA-CMC@PDMA-1 group; 0.5% SA / 2.0% CMC in the SA-CMC@PDMA-2 group).
[0142] Figure 5A as well as Figure 5B The results showed that in the initial acidic environment, the composition of the inner gel structure did not significantly change the sustained release effect of the double-layer hydrogel. Both fat-soluble vitamin A acid (TR) and bovine serum albumin (BS) had good sustained release effects, and water-soluble penicillin (AM) still showed a serious release effect, with a rate of up to 70% to 90% in 2 hours.
[0143] In a weakly alkaline environment, there was no significant difference in the release rates of TR and AM between the two groups. However, SA-CMC@PDMA-2 with a lower SA concentration (the pore size of SA-CMC@PDMA-2 as shown in “1. Gel morphology in electron microscopy” is significantly smaller than that of SA-CMC@PDMA-1) has a better control effect on BS release.
[0144] Compared with the large molecule BS, the fat-soluble TR and water-soluble penicillin AM are both small molecules. Figure 5A as well as Figure 5B It can be found that the composition change of the inner gel structure has little effect on the small molecular content. However, reducing the SA concentration can delay the diffusion rate of the large molecular content and reduce the release rate.
[0145] 3.2.3 Comparison of the outer layer components on the release behavior of the contents
[0146] Please refer to Fig. 6A as well as Figure 6B The difference between the two groups of double-layer composite hydrogel microcarriers lies in the different composition of the outer layer polymer (PDMA in the SA-CMC@PDMA-1 group and PAA in the SA-CMC@PAA-1 group).
[0147] Fig. 6A as well as Figure 6B The results showed that there was no significant difference in the release rates of fat-soluble vitamin A acid (TR) and water-soluble penicillin (AM) in the two groups of double-layer combined hydrogel microcarriers, but the release rate of bovine serum albumin (BS) was significantly reduced when the composition of the outer layer polymer was changed from PDMA to PAA with a lower swelling rate and smaller pore size.
[0148] That is, compared with the use of PDMA, when PAA is used as the component of the outer gel structure, although it has little effect on the small molecular content, it can delay the diffusion rate of the large molecular content and reduce the release rate.
[0149] 4. Structural strength
[0150] In order to test the correlation between the content of a specific component in the gel structure and the structural strength, a single-layer gel structure was prepared according to the steps basically similar to those in point 1.1 of Example 1 and the formulation in Table 2 below, and the correlation between the viscosity of the single-layer gel structure and the temperature was further measured. The results are shown in Figure 7 .
[0151] Table 2. Test group conditions
[0152]
[0153] Figure 7 It is shown that at 37.5°C, as the concentration of carboxymethyl cellulose (CMC) increases, the viscosity of the gel structure increases. It can be understood that when the viscosity of the gel structure increases, it means that the structural strength increases accordingly. Therefore, as the CMC concentration increases, the structural strength of the gel structure also increases accordingly.
[0154] It should be emphasized that when the viscosity approaches or is higher than 1 Pa·s (e.g., SA is 5wt% and CMC is 2wt% in group 1, and SA is 5wt% and CMC is 1wt% in group 2), the structural strength of the gel structure is suitable for culturing stem cells and is not easily broken.
[0155] Relatively speaking, when the viscosity of the gel structure is too low (eg, SA of Group 3 is 5 wt % and CMC is 0.1 wt %), the risk of the gel structure breaking is higher when the gel structure is used to culture stem cells.
[0156] Therefore, when the gel structures of groups 1 and 2 are used as the inner gel structure (the weight percentage of CMC is greater than 1wt%), they can give the double-layer combined hydrogel microcarriers better structural strength to serve as a scaffold for stem cell growth.
[0157] 5. Stem cell culture efficiency
[0158] First, two groups of double-layer composite hydrogel microcarriers with different SA and CMC weight ratios, SA-CMC@PDMA-1 (SA is 1.5% and CMC is 1%) and SA-CMC@PDMA-2 (SA is 0.5% and CMC is 2%) in Table 1 were selected, and adipose stem cells were cultured in a manner similar to Example 2. At the same time, the culture conditions were divided into groups with or without the addition of the nutrient component fetal bovine serum albumin (BSA), and observations were performed simultaneously.
[0159] The following two parts of analysis were then conducted to observe whether the double-layer combined hydrogel microcarriers with different component ratios would affect the growth efficiency of adipose stem cells when used to culture adipose stem cells.
[0160] The first part is mRNA analysis. When the adipose stem cells are cultured for 7 days, the mRNA expression ratio of the unique protein of adipose stem cells (lipoprotein lipase, LPL) and the common protein of cells (glyceraldehyde-3-phosphate dehydrogenase, glyceraldehyde-3-phosphate dehydrogenase, GAPDH) is analyzed to determine the growth of adipose stem cells. The larger the ratio, the higher the content of adipose stem cells. The results are shown in Fig. 8A .
[0161] Fig. 8A It was shown that, regardless of the addition of BSA, SA-CMC@PDMA-1 (SA 1.5% + CMC 1%) had better adipose stem cell growth efficiency compared with SA-CMC@PDMA-2 (SA 0.5% and CMC 2wt%).
[0162] The second part is microscopic observation. The number of cells grown under the microscope was observed in each group of adipose stem cells after 7 days of culture. Adipose stem cells were identified by CD44 monoclonal antibody and stained with Oil RedO, which showed purple-red color. Therefore, the higher the purple-red ratio, the higher the content of adipose stem cells. Figure 8B .
[0163] Figure 8B It is shown that when adding macromolecular nutrient molecules (BSA), the proportion of adipose stem cells in SA-CMC@PDMA-1 (SA1.5%+CMC1%) is higher than that in SA-CMC@PDMA-2 (SA is 0.5% and CMC is 2wt%). In other words, when adding nutrients, the weight ratio condition of SA-CMC@PDMA-1 can have a better stem cell culture efficiency.
[0164] The double-layer composite hydrogel microcarrier provided in some embodiments of the present disclosure is used for the method of culturing stem cells. Through the design of the inner gel structure and the outer gel structure, the inner gel structure can be provided with physical support to avoid the structure being affected by the pH value, and the diffusion resistance can be increased to delay the release of nutrients. By defining the weight ratio of sodium alginate to carboxymethyl cellulose and the position of the nutrients, the pore size of the inner gel structure can be controlled, and the rate of release of nutrients from the double-layer composite hydrogel microcarrier can be regulated, so that the stem cells can stably absorb the nutrients, thereby increasing the growth rate of the stem cells. By controlling the weight percentage of carboxymethyl cellulose, the structural strength of the double-layer composite hydrogel microcarrier can be ensured to serve as a growth scaffold for stem cells.
[0165] Although the present disclosure has been disclosed in the above embodiments, it is not intended to limit the present disclosure. Any person skilled in the art may make various changes and modifications without departing from the spirit and scope of the present disclosure. Therefore, the scope of protection of the present disclosure shall be determined by the appended claims.
Claims
1. A method for culturing stem cells using a double-layer combined hydrogel microcarrier, characterized in that: Include: Provides stem cells, double-layer hydrogel microcarriers and nutrients. The double-layer combined hydrogel microcarrier comprises: An inner layer gel structure, which is obtained by ionically crosslinking an inner layer polymer via an inner layer crosslinker, wherein the inner layer polymer comprises a first inner layer polymer and a second inner layer polymer, the first inner layer polymer is sodium alginate, the second inner layer polymer is carboxymethyl cellulose, the weight ratio of the sodium alginate to the carboxymethyl cellulose is 3:2, and when the weight percentage of the inner layer gel structure is 100%, the weight percentage of the carboxymethyl cellulose is greater than 1%; and The outer layer gel structure is obtained by covalently cross-linking and polymerizing the outer layer monomers through the outer layer cross-linking product, wherein the outer layer gel structure covers the inner layer gel structure. The nutrient component is located inside the inner gel structure; Mixing the stem cells, the double-layer combined hydrogel microcarrier and the nutrient component to obtain a gelled culture medium; as well as The culture medium was added onto the gelled medium.
2. The method according to claim 1, wherein the stem cells comprise embryonic stem cells, hematopoietic stem cells, breast stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells or a combination thereof.
3. The method according to claim 1, wherein: The inner layer gel structure is in the form of a plurality of inner layer sheet structures, and the plurality of inner layer sheet structures are connected to each other and are spaced apart from each other by a plurality of inner layer holes; and The outer layer gel structure is in the form of a plurality of outer layer sheet structures, and the plurality of outer layer sheet structures are connected to each other and spaced apart from each other by a plurality of outer layer holes, wherein the aperture of each outer layer hole is smaller than the aperture of each inner layer hole. 4 . The method according to claim 1 , wherein the inner layer gel structure presents an interpenetrating structure of the first inner layer polymer and the second inner layer polymer.
5. The method according to claim 1, wherein the inner layer polymer and the inner layer cross-linked material have opposite electrical properties. 6 . The method according to claim 1 , wherein the outer layer monomer comprises N,N-dimethylacrylamide, acrylamide or a combination thereof.
7. The method according to claim 1, wherein the outer layer cross-linking material comprises N,N'-methylenebisacrylamide.
8. The method according to claim 1, wherein when the weight percentage of the inner gel structure is 100%, the weight percentage of the sodium alginate is 0.1% to 5%.
9. The method according to claim 1, wherein when the weight percentage of the inner gel structure is 100%, the weight percentage of the carboxymethyl cellulose is 1% to 5%.
10. The method according to claim 1, wherein the nutrient comprises growth factor, vitamin A acid, penicillin, bovine serum albumin or a combination thereof.
11. A method for culturing stem cells using a double-layer combined hydrogel microcarrier, characterized in that: Include: Provide stem cells, a double-layer combined hydrogel microcarrier and nutrients, wherein the nutrients include macromolecular proteins with a molecular weight of at least greater than 500 g / mol, The double-layer combined hydrogel microcarrier comprises: An inner layer gel structure is obtained by ionically crosslinking an inner layer polymer via an inner layer crosslinker, wherein the inner layer polymer comprises a first inner layer polymer and a second inner layer polymer, the first inner layer polymer is sodium alginate, the second inner layer polymer is carboxymethyl cellulose, and the weight ratio of the sodium alginate to the carboxymethyl cellulose is 3:2; and The outer layer gel structure is obtained by covalently cross-linking and polymerizing the outer layer monomers through the outer layer cross-linking product, wherein the outer layer gel structure covers the inner layer gel structure. The nutrient component is located inside the inner gel structure; Mixing the stem cells, the double-layer combined hydrogel microcarrier and the nutrient component to obtain a gelled culture medium; as well as The culture medium was added onto the gelled medium.
12. The method of claim 11, wherein the stem cells comprise embryonic stem cells, hematopoietic stem cells, breast stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells, or a combination thereof.
13. The method according to claim 11, wherein: The inner layer gel structure is in the form of a plurality of inner layer sheet structures, and the plurality of inner layer sheet structures are connected to each other and are spaced apart from each other by a plurality of inner layer holes; and The outer layer gel structure is in the form of a plurality of outer layer sheet structures, and the plurality of outer layer sheet structures are connected to each other and spaced apart from each other by a plurality of outer layer holes, wherein the aperture of each outer layer hole is smaller than the aperture of each inner layer hole. 14 . The method according to claim 11 , wherein the inner layer gel structure presents an interpenetrating structure of the first inner layer polymer and the second inner layer polymer.
15. The method according to claim 11, wherein the inner layer polymer and the inner layer cross-linked material have opposite electrical properties.
16. The method of claim 11, wherein the outer layer monomer comprises N,N-dimethylacrylamide, acrylamide, or a combination thereof.
17. The method of claim 11, wherein the outer layer cross-linker comprises N,N'-methylenebisacrylamide.
18. The method according to claim 11, wherein when the weight percentage of the inner gel structure is 100%, the weight percentage of the sodium alginate is 0.1% to 5%.
19. The method according to claim 11, wherein when the weight percentage of the inner gel structure is 100%, the weight percentage of the carboxymethyl cellulose is greater than 1%.
20. The method according to claim 19, wherein when the weight percentage of the inner gel structure is 100%, the weight percentage of the carboxymethyl cellulose is 1% to 5%.